Agriculture and food security - Badiane, Ousmane (International Food Policy Research Institute, 2009)
After two decades of economic decline and stagnation, Africa has witnessed a remarkable overall economic and agricultural recovery over the last decade. Figure 1 below shows that the average rate of agricultural and overall GDP growth has increased steadily since the middle of the 1990s. More importantly, growth is also spreading to more countries, with an increasing number of countries growing at higher rates towards the end of the period under consideration. The reforms of the 1980s, albeit costly and at times messy, had succeeded in stabilizing African economies after two decades of macroeconomic turmoil. They improved the economic environment and created conditions for the current recovery. Figure 2 shows the sharp decrease in average rates of inflation across the continent, following the reform of the 1980s and the concomitant surge in foreign direct investments. Country fiscal and external trade balances have shown similarly remarkable improvements, as foreign exchange reserves as a share of GDP continued to rise and budgetary deficits fell. African economies became more competitive in international markets. Agricultural exports by African countries grew faster than the world average during the first half of this decade. As a consequence, the share of Africa in global agricultural trade, which had fallen to 2 percent in the late 1980s from 8 percent in the 1960s, rose slightly in the 1990s and has since stabilized around 3%. The absolute value of agricultural and total exports and imports by Africa rose rapidly during the same period.